Mencipta dengan Menghancurkan: Signifikasi Semiotis Kekerasan dan Reproduksi Identitas Sosial - Riyanto, Geger (UI Scholars Hub, 2017)
In this article, I want to show the semiotic signification of violence which made its representation profoundly essential in cultural life. My argument is we cannot fully comprehend the social nature of violence provided we view it merely as an act to satisfy the desire to harm the other or to seize a contested scarce resource. As it gave off the impression of negating the others, violence, whatever its motive, tend to be interpreted as the sign of one’s commitment toward his/her group while considerably strengthening the group’ sense of identity. It is this semiotic signification of violence, I argue, which made it being reproduced prevalently in our cultural imaginations. I will be arguing this by examining cases in which the representation of violence being actively exhibited and exploited to invoke a particular sense of identity.